2016
DOI: 10.1002/ccd.26671
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and hemodynamic results after direct transcatheter aortic valve replacement versus pre‐implantation balloon aortic valvuloplasty: A case‐matched analysis

Abstract: Direct transfemoral TAVR without prior BAV was safe in patients with calcified severe aortic stenosis. Pre-implantation BAV could be omitted in patients undergoing TAVR, without influence in procedure success rate, and subsequent patients' clinical course and valve hemodynamic performance. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
1
14
2
Order By: Relevance
“…Hence, to decrease cerebral emboli during TAVR, emphasis should be made on careful manipulation of catheters in the aortic arch, conscientious anticoagulation, and possibly prophylactic use of an embolic protection device. The present study indicates that BAV during TAVR does not increase the incidence of procedure‐related stroke, which correlates with the bulk of previous evidence . This finding particularly applies to TAVR performed at experienced centers and when third‐generation valves are used.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…Hence, to decrease cerebral emboli during TAVR, emphasis should be made on careful manipulation of catheters in the aortic arch, conscientious anticoagulation, and possibly prophylactic use of an embolic protection device. The present study indicates that BAV during TAVR does not increase the incidence of procedure‐related stroke, which correlates with the bulk of previous evidence . This finding particularly applies to TAVR performed at experienced centers and when third‐generation valves are used.…”
Section: Introductionsupporting
confidence: 90%
“…These results add to the existing data supporting that TAVR can be performed successfully without routine BAV. Omitting this additional step has been shown to be safe, results in successful valve deployment, and yields similar clinical and hemodynamic outcome at up to 1 year . Additional benefits of direct TAVR are lower contrast use and shorter fluoroscopy and procedural time .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Ferrera C, et al, reported a case‐matched analysis in total of 339 patients (102 patients with BAV and 102 direct TAVR) using both self‐expanding and balloon expandable valve platforms which were prospectively selected. A 1:1 matching was conducted, pairing for age, prosthesis type, size, and valvular calcification as 48% of them had moderate to severe valvular calcification.…”
mentioning
confidence: 99%